2020
DOI: 10.3389/fpls.2020.00955
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Response of Cytosolic NO3− to Inorganic Carbon Increase in Posidonia oceanica Leaf Cells

Abstract: The concentration of CO 2 in the atmosphere has increased over the past 200 years and is expected to continue rising in the next 50 years at a rate of 3 ppm•year −1. This increase has led to a decrease in seawater pH that has changed inorganic carbon chemical speciation, increasing the dissolved HCO − 3. Posidonia oceanica is a marine angiosperm that uses HCO − 3 as an inorganic carbon source for photosynthesis. An important side effect of the direct uptake of HCO − 3 is the diminution of cytosolic Cl − (Cl − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…For example, limitation of photosynthesis by light or temperature ( Maberly, 1985 ) or nutrients will decrease inorganic carbon limitation. In addition, Rubio et al. (2020) showed that there was an interaction between nitrate uptake and bicarbonate uptake in P. oceanica .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, limitation of photosynthesis by light or temperature ( Maberly, 1985 ) or nutrients will decrease inorganic carbon limitation. In addition, Rubio et al. (2020) showed that there was an interaction between nitrate uptake and bicarbonate uptake in P. oceanica .…”
Section: Discussionmentioning
confidence: 99%
“…For example, limitation of photosynthesis by light or temperature (Maberly, 1985) or nutrients will decrease inorganic carbon limitation. In addition, Rubio et al (2020) showed that there was an interaction between nitrate uptake and bicarbonate uptake in P. oceanica. High concentrations of HCO − 3 led to loss of cytosolic nitrate via S-type anion channels, which could lead to, or increase, nitrogen limitation.…”
Section: Seagrasses In Past and Future Climatesmentioning
confidence: 99%